PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR DI BEI PERIODE 2022-2024 - Dewi Armanda Parhusip; Hendrik Elisa Sutejo Samosir; Danri Toni Siboro (Jurnal Akuntansi Kompetif, 2026)
This study aims to analyze the effect of profitability and firm size on capital structure in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The study employs a quantitative approach with an associative research method and utilizes secondary data obtained from corporate financial statements. The sample consists of 57 observations selected through purposive sampling. Data were analyzed using panel data regression with EViews 12 software. Capital structure is measured using the Debt-to-Equity Ratio (DER), profitability is proxied by Return on Assets (ROA), and firm size is measured by the natural logarithm of total assets. The results indicate that profitability has a negative and significant effect on capital structure, while firm size has no significant effect on capital structure. Simultaneously, profitability and firm size significantly affect capital structure. The Adjusted R-Squared value of 9.26% suggests that capital structure is also influenced by other factors outside the research model. These findings support the Pecking Order Theory, which explains that more profitable firms tend to rely on internal financing rather than debt financing.